To generate the expression \( 3^{14} \) from \( \frac{3^5}{3^{-9}} \), we used the following properties of exponents:
- The Property of Negative Exponents, which states that \( a^{-n} = \frac{1}{a^n} \) or, rephrased in this context, \( \frac{1}{3^{-9}} = 3^{9} \).
- The Product Rule of Exponents, which states that \( \frac{a^m}{a^n} = a^{m-n} \).
Putting this together, we can rewrite the expression: \[ \frac{3^5}{3^{-9}} = 3^{5 - (-9)} = 3^{5 + 9} = 3^{14} \]
Based on this analysis, the correct response is: the Property of Negative Exponents and the Product Rule of Exponents.